The debate on territorial development and the economy - Samillán Incio, César (2010)
In the context of one of the most relevant world economic-financial crises in the history of the economic system and the increasingly striking evidence of the planet's environmental crisis, the issue of development acquires a priority rethinking that mobilizes academics, politicians and economic and social actors in the search for alternative developments to guide the change of the human social process, given the evident unsustainability of the current logic of growth and development. The territorial development approach constitutes an area of debate in the search for new conceptualizations and strategic definitions that contribute to economic and social change within a framework of sustainability.